Characterization of the cathepsin D in Procambarus clarkii and its biological role in innate immune responses. (October 2020) - Yu, Xiao-Min; Chen, Jia-Le; Abbas, Muhammad Nadeem; Gul, Isma; Kausar, Saima; Dai, Li-Shang
Abstract: Cathepsin D belongs to aspartic protease family, produced in the rough endoplasmic reticulum, and then transported to lysosomes, where it participates in various physiological processes. Despite its importance, only a few reports available on the functional role of cathepsin D in crustaceans. Herein, we cloned a cDNA fragment of cathepsin D from the hepatopancreas of the red swamp crayfish, Procambarus clarkii ( Pc-cathepsin D ) for the first time. It included 1158 base pairs open reading frame, encoding a protein of 385 amino acids. Multiple alignment analysis confirmed the presence of aspartic proteinase active sites and N glycosylation sites. Pc-cathepsin D mRNA expression was high in the gills followed by gut, heart, hepatopancreas of P. clarkii . At different time points post-infection with lipopolysaccharides, peptidoglycan, or polyinosinic polycytidylic acid, Pc-cathepsin D mRNA expression significantly enhanced compared with the control group. Knockdown of the Pc-cathepsin D by double-stranded RNA, strikingly, changed the expression of all the tested P. clarkii immune-associated genes, including Pc-Toll, Pc-lectin, Pc-cactus, Pc-anti-lipopolysaccharide factor, Pc-phospholipase, and Pc-sptzale. Altogether, these results suggest that Pc-cathepsin D is needed to confer innate immunity against microbial pathogens by modulating the expression of crucial transcripts that encode immune-associated genes. Highlights: We identified and characterized cathepsin D cDNA from Procambarus clarkii for the first time. The Pc-cathepsin D ubiquitously expressed in multiple tissues of healthy P. clarkii. The challenge with immune elicitors induced the expression of Pc-cathepsin D in the hepatopancreas. The knockdown of Pc-cathepsin D significantly changed the transcription patterns of immune-associated genes.